2024
DOI: 10.1007/s11207-024-02251-9
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Study of Solar White-Light Flares Observed by the White-Light Solar Telescope of the Lyman-Alpha Solar Telescope on the Advanced Space-Based Solar Observatory (ASO-S/LST/WST) at 360 nm

Zhichen Jing,
Ying Li,
Li Feng
et al.

Abstract: Solar white-light flares (WLFs) are those accompanied by brightenings in the optical continuum or integrated light. The White-light Solar Telescope (WST), as an instrument of the Lyman-alpha Solar Telescope (LST) on the Advanced Space-based Solar Observatory (ASO-S), provides continuous solar full-disk images at 360 nm, which can be used to study WLFs. We analyze 205 major flares above M1.0 from October 2022 to May 2023 and identify 49 WLFs at 360 nm from WST observations, i.e. with an occurrence rate of 23.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…A study that calculates impulsiveness for other lines or bands may reveal that there exists an option for the development of the impulsiveness index that is more directly reflective of the traditionally defined impulsive phase. For example, a recent study by Jing et al (2024) reported on a sample of white-light flares between 2022 October and 2023 May observed in the Balmer continuum at 360 nm by the Advanced Space-based Solar Observatory. While the number of flares captured by this instrument (launched in 2022 October) is currently limited, this is an example of a promising option for determination of an impulsiveness index more useful in explaining the empirical relations between stellar flare impulsiveness and certain spectral quantities.…”
Section: Discussionmentioning
confidence: 99%
“…A study that calculates impulsiveness for other lines or bands may reveal that there exists an option for the development of the impulsiveness index that is more directly reflective of the traditionally defined impulsive phase. For example, a recent study by Jing et al (2024) reported on a sample of white-light flares between 2022 October and 2023 May observed in the Balmer continuum at 360 nm by the Advanced Space-based Solar Observatory. While the number of flares captured by this instrument (launched in 2022 October) is currently limited, this is an example of a promising option for determination of an impulsiveness index more useful in explaining the empirical relations between stellar flare impulsiveness and certain spectral quantities.…”
Section: Discussionmentioning
confidence: 99%
“…The WST can provide full-disk images in the continuum at 3600 ± 20 Å. The pixel size of the images is ≈ 0.5 while the spatial resolution is about 4 (Jing et al, 2024). The cadence is two minutes in a routine mode.…”
Section: Datamentioning
confidence: 99%
“…So far there are only several hundred solar WLFs reported in the literature based on ground-and space-based observations. Generally speaking, the larger flares, say, those of the X and M classes, are more likely identified as WLFs (e.g., Song & Tian 2018;Jing et al 2024).…”
Section: Introductionmentioning
confidence: 99%